2021
DOI: 10.22230/ijepl.2021v17n5a1089
|View full text |Cite
|
Sign up to set email alerts
|

Louisiana School Counselors’ Daily Activities and the ASCA National Model: A Complex History and a Hopeful Future

Abstract: This mixed methods, concurrent nested study was designed to explore the extent to which one state’s school counselors report daily activities that align to the ASCA National Model (ASCA, 2005, 2012, 2019). In spite of federal and state legislation, state policy, and a state model supporting best practices for school counseling, a significant number of school counselors in this study (approximately 25%) report barriers to implementing comprehensive, developmental models. These barriers include inordinate amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…In a related study, Rock and Curry (2021) found that 37% of surveyed school counselors did not implement a comprehensive counseling curriculum that addressed the ASCA Student Standards. Some respondents reported not being “allowed” to facilitate classroom instruction, since teachers could not be asked to give up any instructional time (Rock & Curry, 2021, p. 13). Additionally, in a study of high school counselors, Gruman et al.…”
Section: Present Studymentioning
confidence: 99%
See 3 more Smart Citations
“…In a related study, Rock and Curry (2021) found that 37% of surveyed school counselors did not implement a comprehensive counseling curriculum that addressed the ASCA Student Standards. Some respondents reported not being “allowed” to facilitate classroom instruction, since teachers could not be asked to give up any instructional time (Rock & Curry, 2021, p. 13). Additionally, in a study of high school counselors, Gruman et al.…”
Section: Present Studymentioning
confidence: 99%
“…Given disparities in comprehensive school counseling program implementation, school counselors may benefit from professional development (PD) that fosters an understanding of implementing elements of the ASCA National Model effectively (Kneale et al., 2018; Young & Kaffenberger, 2016). Rock and Curry's (2021) recent study of school counselors’ attempts to implement the model underscored the need for such PD. The researchers found that numerous school counselors who believed they were implementing model elements with fidelity were not, and they did not fully understand what the model's advocated services entailed (Rock & Curry, 2021).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The American School Counselor Association (ASCA, 2019a) 4th Edition National Model (ASCA-NM) discusses the roles of a school counselor and notes that they are trained to do brief counseling to address mental health needs. However, school counselors are often tasked with non-counseling duties, such as test coordination and leading specialized student service meetings, instead of directly working with students and their mental health wellness needs (Rock & Curry, 2021).…”
Section: Introductionmentioning
confidence: 99%